Violet Mackerel's remarkable recovery - Branford, Anna (Atheneum Books for Young Readers, 2012)
With her knack for seeing the positive, six-year-old Violet anticipates extraordinary results after getting her tonsils removed, such as making a special new friend and turning her everyday voice into an opera voice.